Characteristics of Peanut Skin Briquettes and Rice Husk Using the Torefaction Method in a Microwave Oven - Kuntang Winangun; Fauzan Masykur; M. Malyadi; Rendy Cahyono (Universitas Muhammadiyah Sidoarjo, 2019)
Biomass briquettes are an alternative to fossil energy. Biomass briquette material has a large capacity and is easily available in the surrounding environment. The purpose of this study was to determine the value of water content, value of ash content, value of volatile matter content, value of bound carbon content and calorific value of mixed briquettes of peanut shell and rice husk with three different percentages. First a mixture of 30% peanut shell and 70% rice husk, second a mixture of 50% peanut shell and 50% rice husk, third a mixture of 70% peanut shell and 30% rice husk. From the results of the research data, it can be seen that the lowest water content is in a mixture of 70% peanut shells and 30% rice husks of 14.225. The lowest value of ash content was found in a mixture of 70% peanut shell and 30% rice husk at 13.873%. The lowest value of volatile substances was found in a mixture of 30% peanut shell and 70% rice husk at 36.712%. The highest value of bound carbon content was found in a mixture of 30% peanut shell and 70% rice husk at 27.028% and the highest calorific value was found in a mixture of 70% peanut shell and 30% rice husk at 5834.60 cal / g.